Do firms manage their share prices to mitigate investor short-termism? - Bostan, Ibrahim; Lin, Ji-Chai; Mian, G. Mujtaba (Journal of Corporate Finance, 2024)
Recent work documents a behavioral tendency of investors to expect excessively high upside potential for low-priced stocks. These expectations expose low-priced firms to greater pressure for short-term performance because their poor earnings news leads to greater investor disappointment and larger stock price declines. Therefore, we hypothesize that firms with a long-term focus, such as those that invest heavily in research and development (R&D), avoid low share prices. Consistent with our hypothesis, we find that firms with higher R&D capital decide on a higher filing price in their initial public offering, are less likely to undergo a stock split once listed, and upon a stock split, choose a higher post-split price. We establish a causal link between firms' R&D and share price management by exploiting the exogenous increases in R&D expenditures induced by the staggered introduction of state-level R&D tax credits in the US. Our study suggests that firms with large R&D capital target high share prices to shield their long-term investments from investor short-termism.